Analisis Akuntansi Pertanggungjawaban Sosial Sebagai Bentuk Tanggung Jawab Perusahaan terhadap Lingkungan Sekitarnya : Studi Kasus PT. Bank Syariah Indonesia Cabang Bandar Lampung - Nurmila Nurmila; Ersi Sisdianto (Jurnal Riset Akuntansi, 2024)
Social responsibility is another form of achievement of a financial institution. This is a form of responsibility that must be given especially to the surrounding area. BSI Bandar Lampung has carried out tourism empowerment as a form of social responsibility. To find out accountability reporting must be done in a good form of accountability. So the aim of this research is to analyze the accountability of social responsibility reporting carried out by BSI Bandar Lampung. This research is qualitative in nature with informants from the treasurer of BSI Bandar Lampung. The results of this research show that Bank BSI Bandar Lampung has implemented corporate social responsibility in the form of corporate social activities outlined in the form of partnership programs and environmental development. The implementation of corporate social responsibility accounting at BSI Bandar Lampung bank is less than optimal. There is no special report from the company for a detailed breakdown of CSR costs. CSR costs are included in non-operational items and included in the central BSI bank's annual financial report. The form of BSI Bandar Lampung bank's social activities is in accordance with applicable regulations